Risk factors and comorbidities associated with magnesium deficiency in pregnant women and women with hormone-related conditions: analysis of a large real-world dataset - Svetlana Orlova; Galina Dikke; Gisele Pickering; Natalya Yaltseva; Sofya Konchits; Kirill Starostin; Alina Bevz (BMC, 2021)
Abstract Background An accumulating body of literature indicates that magnesium deficiency is associated with a number of hormone-related conditions (HRC) in women, and epidemiological studies are needed to assess its prevalence and risk factors. Here, we present a secondary analysis of data pooled from four large observational studies that assessed magnesium deficiency among pregnant women and women with HRC across the Russian Federation. Methods The main objective of this analysis was to estimate the prevalence of magnesium deficiency in this population and to describe risk factors and comorbidities associated with low serum magnesium. Univariate logistic regression analysis was performed to identify the risk factors and comorbid conditions associated with an increased risk of low serum magnesium level. Results A total of 983 pregnant women and 9444 women with HRC were eligible for analysis. Prevalence of hypomagnesemia (magnesium serum level cut-off < 0.66 mmol/L/< 0.8 mmol/L) was 34.0%/78.9% in pregnant women and 21.4%/54.8% in women with HRC. The highest prevalence of magnesium deficiency was observed for osteoporosis and climacteric syndrome. Risk factors included diastolic blood pressure, previous pregnancy complications, infections and edema for pregnant women, and age, body mass index, and various comorbidities for women with HRC. Conclusions These results confirm the high prevalence of hypomagnesemia in pregnant women and women with HRC and underline the importance of routine screening, since risk factors are mostly non-specific.